Effectiveness of Absorption Wells Using The Sunjoto Method to Control Flooding in The Village of Ngraseh Bojonegoro - Mushthofa, Mushthofa; Fadhila, Fajrina Nur; Indriani, Yulia; Faqih, Nasyiin; Qomaruddin, Mochammad (Journal of Green Science and Technology, 2024)
Infiltration wells are a form of hydrological infrastructure used to manage rainwater. Infiltration wells are usually built as part of a rainwater management system to soak rainwater into the ground and reduce surface waterlogging as well as slow down surface runoff and allow rainwater to seep into the ground to renew aquifers or prevent waterlogging. Maintaining groundwater levels is an important step in sustainable water resource management. The aim of this research is to plan effective infiltration wells to replace rainwater catchment areas lost due to building construction. The planning of this infiltration well uses the Sunjoto  method. From the research results, it was found that an effective infiltration well design was calculated using the Sunjoto  method. With the data, each roof area of ​​the house has an optimum number of infiltration wells with a planned infiltration well diameter of 1 m with a depth of 2.5 m with an effective depth according to the calculations is as follows: 60 m2 number of 1 unit of absorption well with an optimum depth of 2.82 m, 80 m2 number of 2 units of absorption well with an optimum depth of 3.76 m, 100 m2 number of 2 units of absorption well with an optimum depth of 4.7 m, 120 m2 number of 2 units of infiltration wells with an optimum depth of 5.64 m, 140 m2 number of 3 units of absorption wells with an optimum depth of 6.58 m, 160 m2 number of 3 units of absorption wells with an optimum depth of 7.52 m, 180 m2 number of 3 units of absorption wells with an optimum depth of 8.46 m, 200 m2 total of 4 units of infiltration wells with  an  optimum depth  of 9.4 m.